The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2023
DOI: 10.3390/app13169209
|View full text |Cite
|
Sign up to set email alerts
|

Anticancer Activity of Mineral-Supplemented Organically Cultivated Carrot on HT-29 Cells and Its Anti-Inflammatory Effect on Mice Splenocytes

Yanni Pan,
Yeon-Jun Lee,
Sin-Il Sin
et al.

Abstract: Carrot (Daucus carota) is one of the world’s most significant root vegetables, with various bioactivities. This study aimed to investigate the anticancer activity and anti-inflammatory effects of natural dream cultivation carrot (NC). Natural dream cultivation is a cultivation method based on organic farming incorporating minerals. An MTT assay was used to evaluate the inhibitory rate of carrot samples on HT-29 human colon cancer cells, and qPCR was used to assess the mRNA expression of the cell cycle and apop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 54 publications
0
3
0
Order By: Relevance
“…Although moderate NO production assists in pathogen clearance, excessive NO production might induce tissue damage and exacerbate infammatory reactions [26]. Research fndings suggest that under immune stimulation, such as exposure to LPS, the expression and activation of iNOS in RAW 264.7 cells and mice splenocytes increase, resulting in elevated NO production that participates in immune and infammatory regulation [4,5]. Our evaluation of NO generation after LPS treatment revealed signifcantly lower NO production in the sample-treated groups than in the LPS-treated group.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Although moderate NO production assists in pathogen clearance, excessive NO production might induce tissue damage and exacerbate infammatory reactions [26]. Research fndings suggest that under immune stimulation, such as exposure to LPS, the expression and activation of iNOS in RAW 264.7 cells and mice splenocytes increase, resulting in elevated NO production that participates in immune and infammatory regulation [4,5]. Our evaluation of NO generation after LPS treatment revealed signifcantly lower NO production in the sample-treated groups than in the LPS-treated group.…”
Section: Discussionmentioning
confidence: 99%
“…During infection, trauma, and tissue damage, IL-6 production increases, promoting immune cell activation and infammatory responses [32]. Based on multiple research fndings, it has been shown that LPS has an impact on RAW 264.7 cells and splenocytes by increasing the levels of infammatory cytokines, including TNF-α, IL-1β and IL-6 [4,5,[33][34][35].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation